Phenotypic and Genotypic Traits of Vancomycin-Resistant Enterococci from Healthy Food-Producing Animals - Wist, Valerie (Microorganisms, 2020)
Food-producing animals may be a reservoir of vancomycin-resistant enterococci (VRE), potentially posing a threat to animal and public health. The aims of this study were to estimate the faecal carriage of VRE among healthy cattle (n = 362), pigs (n = 350), sheep (n = 218), and poultry (n = 102 flocks) in Switzerland, and to characterise phenotypic and genotypic traits of the isolates. VRE were isolated from caecum content of six bovine, and 12 porcine samples respectively, and from pooled faecal matter collected from 16 poultry flock samples. All isolates harboured vanA. Three different types of Tn1546-like elements carrying the vanA operon were identified. Conjugal transfer of vanA to human Enterococcus faecalis strain JH2-2 was observed for porcine isolates only. Resistance to tetracycline and erythromycin was frequent among the isolates. Our data show that VRE harbouring vanA are present in healthy food-producing animals. The vanA gene from porcine isolates was transferable to other enterococci and these isolates might play a role in the dissemination of VRE in the food production chain.